HIBP diagnostic injectors for Uragan-2M and TJ-II stellarators - Bondarenko, I.S.; Chmyga, A.A.; Deshko, G.N.; Komarov, A.D.; Kozachek, A.S.; Krupnik, L.I.; Khrebtov, S.M.; Taschev, Yu.I.; Zhezhera, A.I. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The testing and first operations of the Heavy Ion Beam Probe (HIBP) plasma diagnostic injectors for stellarator Uragan-2M and TJ-ІІ is presented in this work. The increasing of plasma density in modern fusion devices up to (3...7)×10^19m^-3 (TJ-ІІ and T-10) leads to huge probing ion beam absorption in central plasma area. One way to obtain the HIBP information from plasma centre is the increasing of primary ion beam current. A new modification of HIBP injectors for TJ-ІІ and Uragan 2M stellarators was developed and tested in IPP NSC KIPT with energy up to 100 keV and ion current up to 300 μA.